Re-reading Italian Americana : Specificities and Generalities on Literature and Criticism - Tamburri, Anthony Julian (Fairleigh Dickinson University Press series in Italian studies., 2013)
Re-reading Italian Americana broadens the scope of Italian/American literary criticism by investigating the work of six authors and the degree to which they successfully represent Italian Americana in their prose or poetry. Highlighting the work of Pietro di Donato, Mario Puzo, Luigi Barzini, Joseph Tusiani, Maria Mazziotti Gillan, and Rina Ferrarelli, this book examines the current state of analysis dedicated to this topic and its reception both in the United States and in Italy.